THE SYSTEMATIC REVIEW OF STRESS URINARY INCONTINENCE - Amal Ramadhani, Rizkia (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: Stress urinary incontinence (SUI) affects around 400,000 women in Switzerland, constituting 60 of cases, with symptoms impacting daily life for over 77.5 of affected individuals, especially those over 40 and in nursing homes. The condition, often triggered by activities like laughing or coughing, ranges from minor leaks to more substantial urine loss, significantly affecting quality of life due to weakened pelvic muscles and other factors like menopause and obesity. Treatment options, from pelvic exercises to surgical procedures, require individualized care and a collaborative healthcare approach. This review aims to explore these advancements, focusing on recent studies in SUI management. Methods: The researchers in this study followed the 2020 Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines to ensure that their work met the required standards. This was done to ensure the precision and reliability of the conclusions derived from the research. Result: Our search produced 14 results. After looking at the titles and summaries, we discovered 12 papers that fit our criteria after excluding several articles because they did not fit into criteria. But after reading the full papers carefully, we included five papers in our final analysis. These papers included a retrospective observational study and several case reports. Conclusion: Stress urinary incontinence (SUI) affects around 400,000 women in Switzerland, constituting 60 of cases, with symptoms impacting daily life for over 77.5 of affected individuals, especially those over 40 and in nursing homes. The condition, often triggered by activities like laughing or coughing, ranges from minor leaks to more substantial urine loss, significantly affecting quality of life due to weakened pelvic muscles and other factors like menopause and obesity. Treatment options, from pelvic exercises to surgical procedures, require individualized care and a collaborative healthcare approach. This review aims to explore these advancements, focusing on recent studies in SUI management